Relation Between Metabolic Activity of the Broca Region and F-18 FDG Uptake in Vocal Cords - Eren, Mine Şencan (Galenos Publishing, 2012)
Objective: We aimed to investigate if increased F-18 Fluoro Deoxyglucose (F-18 FDG) uptake observed in vocal cords (VC) of the patients on Positron Emission Tomography/Computarize Tomography (PET/CT) scans is connected to speaking of the patients or not. If so, we expected to detect an increased metabolic activity in Broca's area. In this study, we have retrospectively searched for a correlation between the activity in the Broca's area and vocal cords of patients who had undergone FDG PET for different indications. Material and Methods: FDG PET/CT scans of 30 patients with (VC [+]) and 30 patients without (VC [-]) bilateral F-18 FDG uptake on their vocal cords were retrospectively evaluated. Brain quantification was carried out on NeuroQ software with 20 iterations using patients' transaxial brain cross sections. On the 20th-23rd-26th-29th cross sections, area/whole brain ratios of the right (R) and left (L) for Broca’s area were calculated. VC (+) and VC (-) patients' R and L Broca's areas were compared using Student's t-test. Results: There was no significant difference between the Broca's areas of VC (+) and VC (-) patients. L Broca's areas of both VC (+) and VC (-) patients were more active than R Broca's areas (p<0.05). There was a negative correlation between VC (+) patients' SUVmax values in the vocal cords and the activity in their R Broca's region. Conclusion: In our study, we did not find a significant difference between Broca's areas of VC (+) patients and VC (-) patients, so the activity in their vocal cords does not seem to be related to increased metabolic activity in Broca's areas. We have concluded that the vocal cord activity is not related to speaking of the patients. The activity in the vocal cord might be due to inflammation or, as in the eye muscles, may be associated with high metabolism in laryngeal muscles. Conflict of interest:None declared.